Interbank transactions on the intraday frequency: - Different market states and the effects of the financial crisis - - Anastasios Demertzidis (Philipps-University Marburg, School of Business and Economics, 2019)
The focus of this paper lies in the study of the intraday distribution of the number of transactions and transaction volume (absolute and mean per transaction) in the interbank credit market e-MID in different market states around the events of the financial crisis of 2007. The results show that the distributions of the number and of the volume of transactions can be characterized as U-shaped and the distribution of the mean per transaction as three-peaked. However, there are important differences when it comes to the comparison of the different market states and the differentiation between sell and buy transactions. Moreover, this study detects stylized facts about the market regarding the number of trades and the volume during the day. Sell transactions are higher in each market state. This highlights the fact that this market is used widely to deposit excessive liquidity in all intervals during the day. Furthermore, differences within these variables during different market states can be observed, which highlights the importance of this analysis. This study can strengthen our understanding of the interbank credit market as it is important for policy makers and the daily trading strategies of banks. Additionally, implications can be seen as the basis for further empirical and econometric research.
Keywords: C46; G01; G12; G15; Y10; 330; interbank credit market; e-MID; intraday frequency; financial crisis